Implementasi Peraturan Menteri Ketenagakerjaan Nomer 5 Tahun 2012 tentang Sistem Standarisasi Kerja Nasional - Febry Bernadetta; Yuwanto .; Susilo Utomo (Journal of Politic and Government Studies, 2017)
The National Work Standardization System is a community empowerment facilitator as well as a set standard for assessing the skills and skills of the workforce to be relevant to competency-based needs and able to compete globally. The National Standardization of Working System covering in training, apprenticeship, certification of labour which has been listed in the Regulation of the Minister of Manpower Number 5 of 2012.The purpose of this research is to know how Implementation of Regulation of Minister of Manpower Number 5 of 2012 which refers to National Work Standard System at Semarang Labour Training Center as well as any factors that support and inhibit the success of the effective national working standard system. This research uses qualitative method to describe how the training activity of Indonesian Workers in Semarang Training Center of Semarang in terms of labor and trainer instructor by using theory of implementation study and public policy as research guideline.Based on the Research Result that the Implementation of National Work Standardization System in the training of Workers at Semarang Training Center of Semarang runs less effective because of collision in the convoluted communicationbecause of the many levels of long bureaucracy and lack of discipline of his attitude in every policy actors so not all The workforce has the ability to be competent in accordance with the syllabus that has been set in the Regulation of Minister of Employment Number 5 of 2012. But in terms of facilities, funding, and the allocation of training time with the curriculum can be said to be effective implementation. Suggestion given for the quality improvement of worker trainingprogram at Semarang Labour Training Center is the need to do strictly instructor sorting with competent foreign language skills test so that instructors who train the workforce are not only  ex-Labour who are competent but Also a person who has the ability to teach so that the workforce is really effective in carrying out the training and their ability can be in accordance with the National Standardized Working System in the set.  Keywords:  Implementation, Regulation of the Minister of Manpower,               National Work Standardization System, Training, Manpower.